Analisis Kemampuan Menulis Teks Deskripsi Siswa Kelas V SD Negeri Kemuning - Iroh Rojatu Tadzkiroh; Muryani Muryani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Writing descriptive essays is one of the basic competencies of the 2013 Curriculum implemented in class V of SD Negeri Kemuning. The goal to be achieved in this study is to describe the ability to write descriptive essays for fifth grade students of SD Negeri Kemuning based on the results of performance tests. This research uses descriptive qualitative research through a case study approach. In the differentiated learning activities carried out by the teacher in the classroom, the source of the data in this study was a document in the form of a student's description essay. The ability to write essay descriptions of students is included in the sufficient category with a score range of 60-70. Students' ability to write descriptive essays is influenced by students' difficulties in writing, namely difficulties in expressing ideas, developing sentences, determining good and correct spelling, and concentrating.